A Solid State Plasma Multifunctional Metamaterial and Its Application for Energy Absorbing and Cross Polarization Conversion - Li Zeng (IEEE Access, 2020)
With the increasing expectations of electromagnetic devices, the defects of monofunctional devices that are susceptibly limited by external constraints are becoming more and more obvious and the integration of multiple functions has gradually become the pursuit of researchers. In this paper, a novel multifunctional metamaterial tailored by the solid state plasma (SSP) is proposed. By inspiring the particular SSP resonators, such a metamaterial can be handily switched back and forth among two functions and form three working states. When the proposed SSP metamaterial is served in State I, its function embodies as an energy absorber and the absorption which is over 90% for TE and TM modes are 5.84-7.30 GHz and 5.41-6.34 GHz whose relative bandwidths (RBs) are 22.22% and 15.83%, respectively. States II and III keep the same functionality of cross-polarization conversion but a distinct operating band. The polarization conversion rate (PCR) of State II which is higher than 90% is 7.40-12.20 GHz (the RB is 48.98%) and this operational range will be shifted to 5.71-8.47 GHz (the RB is 38.92%) after switching to State III. Compared with the conventional tunable devices, this SSP metamaterial has the advantage of functional diversity and it provides a new design idea of absorber and polarization converter to promote potential applications of multifunctional devices.